Analysis of hard coral condition on coral reef ecosystem in Ternate Island. Issue 1 (October 2021) - Paembonan, R E; Ismail, F; Baddu, S; Najamuddin,; Tahir, I; Akbar, N; Inayah,; Nurhayati, A
Abstract: Hard coral is a type of coral building structure in coral reef ecosystems. Hard coral is a coral reef entity that plays an important function in a coral reef ecosystem, especially related to physical and ecological functions in shallow marine waters environment. This study aimed to study percentages of coral cover, species life form, diversity index, dominance index, and distribution clusters of hard corals based on environmental parameters around Ternate Island. Hard coral cover sampling was carried out systematically using the underwater photo transect (UPT) method. The number of sampling stations were 30 location points with 750 photos. The method used for analyzing ecological conditions of hard corals was coral point count with excel extensions (CPCe). Environmental parameters measured included salinity, temperature, pH, brightness level, and dissolved oxygen. The distribution of hard coral clusters was analyzed statistically using the classify-hierarchical cluster. Study results showed that coral cover percentages ranged from 19% to 93% with an average cover of 67%, species diversity range was 7 to 40 species with an average of 19 species, diversity index (H ') with a value of 1.14 to 6.02 with an average of 2.07, dominance index (D) with a value of 0.13 to 0.53 with an average of 0.23. The results of the analysis of the distribution of hard corals consisted of four clusters. The study also found that distribution of hard coral clusters in Ternate Island was related to substrate topography.